1995
DOI: 10.1021/bp00033a005
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Coated Lipase Suitable for the Enzymatic Resolution of Menthol as a Biocatalyst in Organic Media

Abstract: Enantioselective esterification of menthol with fatty acids using a surfactant‐coated lipase was carried out in organic media. The surfactant‐coated lipase originating from Candida cylindracea appeared to be highly enantioselective and good biocatalyst for the resolution of racemic menthol. The enzymatic activity of the lipase in organic media was significantly increased by a coating with a nonionic surfactant. The reaction rate of the coated lipase was more than 100 times that of the powder lipase. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 24 publications
3
43
0
2
Order By: Relevance
“…At 30°C, nearly 50% of (−)-menthol was converted to the ester form after 48 h incubation. The reaction rate was comparable to enzymatic resolutions of (±)-menthol obtained previously with lipase from C. cylindracea (1,12).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…At 30°C, nearly 50% of (−)-menthol was converted to the ester form after 48 h incubation. The reaction rate was comparable to enzymatic resolutions of (±)-menthol obtained previously with lipase from C. cylindracea (1,12).…”
Section: Resultssupporting
confidence: 81%
“…In recent years, the use of lipases as biocatalysts for enzymatic resolution of racemic substances has increasingly attracted research interest because of their demonstrated high enantioselectivity compared to chemical catalysts (1). In addition, lipases are readily available, relatively inexpensive, and have no cofactor requirement (2).…”
mentioning
confidence: 99%
“…nonionic, cationic, anionic and zwitterionic), surfactants are useful for modulating certain interactions. Therefore, the effect of surfactant on lipase interactions would depend strongly on the choice of both lipase and surfactant included in the reactions (Kamiya et al, 1995). It was observed that after 11 h of reaction, the Triton X-100 (non-ionic) yielded the highest percentage of acid conversion for CRL-MWCNTs (to 83.62%) when compared with that of free…”
Section: Effect Of Surfactantsmentioning
confidence: 99%
“…Lipase-catalyzed esterification [4][5][6] and transesterification [1,7] reactions in organic solvents have been commonly used for the enantioselective resolution of racemic mixtures. Recently, ketoreductase-catalyzed reactions [8][9][10][11][12] have been used for the production of chiral secondary alcohols from the corresponding ketones.…”
Section: Introductionmentioning
confidence: 99%